Beginning iOS application development with HTML and JavaScript - Wagner, Richard 1966- (Indianapolis, IN John Wiley & Sons, 2012)
Annotation Web developers with HTML/JS skills will quickly learn to apply them to the iPhone/iPad platformBeginning to intermediate web developers who want to apply their existing HTML/CSS/JS/Ajax skills to the wildly popular iPhone/iPad OS will love this book. In the highly successful Wrox Beginning format, it enables developers who know these core technologies to use what they already know and get up to speed quickly. It introduces iOS development with web technologies, explains how to enable and optimize web sites for the iPhone and iPad, explores user interface design, then moves into animation, special effects, building with web frameworks, and much more.Teaches you to apply your knowledge of HTML, JavaScript, and related web technologies to the iOS platform and create apps for the iPad and iPhoneExplains how to enable and optimize web sites for the mobile screen, design an effective iPad and iPhone UI, and apply CSSCovers building in interactivity, animation, and special effects, programming the canvas, offline, apps, bandwidth performance and optimization, and web frameworksShows you how to package your app inside a native iOS wrapper (no programming required) so you can submit your apps to the App StoreDevelopers who already know HTML and JavaScript can get up to speed on iOS app development more quickly with the help of this Wrox guide --
Part 1. Getting started. Introducing iOS development using web technologies -- Working with core technologies -- The document object model -- Writing your first hello world application -- Enabling and optimizing web sites for the iPhone and iPad -- Part 2. Application design. Designing the iPhone UI -- Designing for iPAD -- Styling with CSS -- Part 3. Application development. Programming the interface -- Handling touch interactions and events -- Special effects and animation -- Integrating with iOS services -- Packaging apps as bookmarks : bookmarklets and data URLS -- Part 4. Advanced programming techniques. Programming the canvas -- Offline applications -- Building with web app frameworks -- Bandwidth and performance optimizations -- Debug and deploy -- Part 5. Next steps: developing native iOS applications with HTML and JavaScript. Preparing for native iOS development -- PhoneGap : native apps from your HTML, CSS, and JavaScript -- Submitting your app to the app store
"Wrox programmer to programmer"--Cover
Includes index
1
Keywords: iOS (Electronic resource); Apple iPad (ordinateur); Application software -- Development; HTML (Document markup language); HTML (langage de balisage); JavaScript (Computer program language); JavaScript (langage de programmation); iPad (Computer) -- Programming; iPhone (Smartphone) -- Programming; iPhone (smartphone)